Gender Difference of Politeness Strategies Through Online Chatting Experienced by EFL Students in Al-Anbar Distinguished Schools - Hamood, Baydaa Subhi; Challob, Ala’a Ismael (Al-Adab Journal, 2023)
The aim of this paper is to identify the differences between male and female politeness strategies employed by Iraqi EFL students in Al-Anbar Distinguished Schools. To attain this aims, the participants of the study were selected from Al-Anbar Distinguished Schools, represented by 53 female students and 50 male students during the academic year (2021-2022) to be in direct and frequent online interaction (via text messages) with each other as students, and with their teachers of English language. Consequently, WhatsApp and Telegram groups were created for this online chatting. A qualitative research design was conducted whereby online text chatting was collected to ensure the data of this study. The collected data were analyzed qualitatively by using content analysis procedure based on Brown’s and Levisohn’s (1987) model of politeness strategies. The findings showed that there were differences between males and females’ use of politeness strategies as female students used these strategies slightly more than male students. It is worth noting that female students have used negative politeness strategies more than male students. Accordingly, teachers and students’ parents must educate students about how to use these strategies properly in communication especially via online chatting.